THE IMPACT OF THE FINANCIAL RESULT OF THE CHANGE IN VENTURE CAPITAL: PRACTICAL ASPECTS - Jalaghonia, David (Business and Legislation, 2014)
The paper deals with issues related to the impact of the fi nancial result of the change in ven-ture capital. Studied and analyzed in the theoretical and practical aspects of income and expense accounting. Based on the example provided accounting procedures, which are directly related to the income statement, statement of changes in equity and the accounting balances.